2016
DOI: 10.1007/s10729-015-9350-2
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic multi-objective auto-optimization for resource allocation decision-making in fixed-input health systems

Abstract: The management of hospitals within fixed-input health systems such as the U.S. Military Health System (MHS) can be challenging due to the large number of hospitals, as well as the uncertainty in input resources and achievable outputs. This paper introduces a stochastic multi-objective auto-optimization model (SMAOM) for resource allocation decision-making in fixed-input health systems. The model can automatically identify where to re-allocate system input resources at the hospital level in order to optimize ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, it is perhaps in the best interest not to actively influence further reduction in doctor–patient interaction time. Hence this variable has been included in the queuing–DEA model as a “non-discretionary” output with a view of keeping it constant; as opposed to previous DEA studies where “non-discretionary” inputs are considered such as treatment population (Mitropoulos et al ., 2013; Bastian et al , 2017) and number of beds (Herwartz and Strumann, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is perhaps in the best interest not to actively influence further reduction in doctor–patient interaction time. Hence this variable has been included in the queuing–DEA model as a “non-discretionary” output with a view of keeping it constant; as opposed to previous DEA studies where “non-discretionary” inputs are considered such as treatment population (Mitropoulos et al ., 2013; Bastian et al , 2017) and number of beds (Herwartz and Strumann, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This approach draws parallels to previous work by Bastian et al, which developed the Stochastic Multi-Objective Auto-Optimization Model for resource allocation in fixed-input health systems. 11 This model automatically identifies optimal re-allocation of system input resources at the hospital level, considering the uncertainty in model parameters, and has been applied to 128 hospitals across the nation. Part of this paper highlights the importance of considering uncertainty in performance measurement systems.…”
Section: Related Workmentioning
confidence: 99%
“…It was suggested that for a complex non-trivial problem of this kind, a hybrid approach combining several optimisation techniques might be successful. Bastian et al [91] optimised resources across the United States Military Hospital System using mixed-integer linear programming, including some stochastic elements, but this was only for staff and funding. Another study by Feng et al [92] produced a multi-objective stochastic mathematical model for medical resource allocation in emergency departments.…”
Section: Core Activitiesmentioning
confidence: 99%